Dealing with Stress: Defective Metabolic Adaptation in Chronic Obstructive Pulmonary Disease Pathogenesis - Michaeloudes,C; Bhavsar,PK; Mumby,S; Chung,KF; Adcock,IM (Annals of the American Thoracic Society, 2017)
The mitochondrion is the main site of energy production and ahub of key signaling pathways. It is also central in stress-adaptiveresponse due to its dynamic morphology and ability to interactwith other organelles. In response to stress, mitochondria fuseinto networks to increase bioenergetic efficiency and protectagainst oxidative damage. Mitochondrial damage triggerssegregation of damaged mitochondria from the mitochondrialnetwork through fission and their proteolytic degradation bymitophagy. Post-translational modifications of themitochondrial proteome and nuclear cross-talk lead toreprogramming of metabolic gene expression to maintain energyproduction and redox balance. Chronic obstructive pulmonarydisease (COPD) is caused by chronic exposure to oxidativestress arising from inhaled irritants, such as cigarette smoke.Impaired mitochondrial structure and function, due tooxidative stress–induced damage, may play a key role incausing COPD. Deregulated metabolic adaptation maycontribute to the development and persistence of mitochondrialdysfunction in COPD. We discuss the evidence for deregulatedmetabolic adaptation and highlight important areas forinvestigation that will allow the identification of moleculartargets for protecting the COPD lung from the effects ofdysfunctional mitochondria.